2017
DOI: 10.21276/apalm.2017.982
|View full text |Cite
|
Sign up to set email alerts
|

Superoxidised water: A promising disinfectant against bacterial and fungal pathogens

Abstract: Background: Disinfectants are frequently used in hospital settings as prophylaxis. Superoxidised water is one of them, which is claimed to have disinfectant property against different microbes. Aim:This study aims to assess the in vitro efficacy of different dilutions of superoxidised water against Candida spp. and filamentous fungi apart from several pathogenic bacterial isolates. Material and Methods:The freshly grown clinical isolates of selected bacteria and fungi including Candida spp.,Aspergillus sp., Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Superoxidised water (SOW) is a newer disinfectant which has the ability to kill the microbes within the seconds of exposure. In previous studies, its efficacy has been assessed against the different bacterial and fungal pathogens including yeast and filamentous fungi 9 . In this present study, we assessed the efficacy of the freshly generated SOW against the Trichophyton spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxidised water (SOW) is a newer disinfectant which has the ability to kill the microbes within the seconds of exposure. In previous studies, its efficacy has been assessed against the different bacterial and fungal pathogens including yeast and filamentous fungi 9 . In this present study, we assessed the efficacy of the freshly generated SOW against the Trichophyton spp.…”
Section: Discussionmentioning
confidence: 99%
“…It also impairs the solute transport as well as the salt balance, resulting in the cell lysis 8 . Potent disinfectant role of superoxidised water against bacteria and molds has been reported by different authors but, Best of our knowledge, no in vitro study has been conducted against the dermatophytes [9][10][11] . Against this background, we assessed the in-vitro activity of superoxidised water (SOW) against the dermatophytes isolated from skin lesions.…”
Section: Introductionmentioning
confidence: 99%
“…They may also be referred to as super-oxidised water, or most commonly by product names. § Bench research reports that SOSs have antibacterial [1][2][3]6,7 , antiviral 5 and antifungal 1 qualities against strains commonly observed in chronic wounds, including antibiotic-resistant bacteria 2 and biofilm based organisms 20,21 . There is laboratory-based evidence that they reduce inflammatory markers 4 (Level 5).…”
Section: Introductionmentioning
confidence: 99%
“…
Super-oxidised solutions are a low cost topical antiseptic option for chronic wounds. Antibacterial, antimicrobial and anti-fungal properties of SOSs have been established in laboratory research [1][2][3][4][5][6][7]. Level 1 evidence from a systematic review 8 and a randomised controlled trial (RCT) 9 showed SOS was as effective as povidone iodine in reduction microbial bioburden.
…”
mentioning
confidence: 99%
“…Moreover, the inoculation of electrolyzed water was able to inhibit periodontopathogens such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Prevotella intermedia, and Treponema denticola[22,29,32,35, 38,41,42,45,49,50,54, 56], by signi cantly reducing the percentage of viable bacteria or their CFU number after treatment. In addition, pathogens commonly found on infected canals, such as E. faecalis and Porphyromonas endodontalis, were also sensitive to electrolyzed water, showing signi cantly reduced CFU numbers and viability in a time-dependent manner[29,31,37,39,43,52,55]. Apart from that, electrolyzed water also showed antifungal activity by inhibiting the growth and diminishing the mean CFU counts of Candida albicans cultures in nine studies[29, 31, 34-36, 47, 52, 59, 60] (Table3).…”
mentioning
confidence: 99%